2014
DOI: 10.1155/2014/813286
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Quality Characteristics of Taftoon Bread as Affected by Salep and Persian Gums

Abstract: Effects of salep gum at concentrations of 0.5%, 1%, 3%, and 5% (w/w flour basis) and the Persian gum at concentrations of 0.5%, 1%, and 3% (w/w flour basis) and combination of the two gums at concentrations of 0.5% + 0.5%, 0.75% + 0.25%, and 0.25% + 0.75% on rheological properties of the wheat flour dough and quality of Taftoon bread were studied with regard to retardation of staling. Rheological (farinograph and extensograph) characteristics, staling, and organoleptic evaluations were performed on the dough a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…It was noticed from the pictures in figures ,The result of Scanning Electron Microscopic that addition fenugreek gum at concentration of 2% had improved the composition of bread as it was characterized by the presence of starch granules and good distribution of moisture inside the bread compared the control at different temperatures storage for 1 and 7 days .Addition of fenugreek gum cause delaying the staling bread due to the high moisture consent of the bread containing gum was to bond with water through the hydroxyl groups in its composition and retained by preventing the formation of ice crystals during storage [16,17] , the result was agreement with [13] and agree also with [18].…”
Section: Scanning Electron Microscopic (Sem)supporting
confidence: 77%
“…It was noticed from the pictures in figures ,The result of Scanning Electron Microscopic that addition fenugreek gum at concentration of 2% had improved the composition of bread as it was characterized by the presence of starch granules and good distribution of moisture inside the bread compared the control at different temperatures storage for 1 and 7 days .Addition of fenugreek gum cause delaying the staling bread due to the high moisture consent of the bread containing gum was to bond with water through the hydroxyl groups in its composition and retained by preventing the formation of ice crystals during storage [16,17] , the result was agreement with [13] and agree also with [18].…”
Section: Scanning Electron Microscopic (Sem)supporting
confidence: 77%
“…Sahari et al . () also reported that adding salep gum to wheat flour increased water absorption significantly. The effect is due to the presence of hydroxyl groups in the hydrocolloid structure that allow more water interaction through hydrogen bonding (Glicksman ; Rosell et al .…”
Section: Resultsmentioning
confidence: 87%
“…The results indicated that 48 hr of storage was the optimal storage time for both flatbreads. Sahari, Mohammadi, and Hamidi Esfehani (2014) also showed that with increasing the shelf life of the "Taftoon" flatbread, its Kramer shear force and its firmness levels increased.…”
Section: Mechanical Flatbread Test Resultsmentioning
confidence: 90%
“…The results indicated that 48 hr of storage was the optimal storage time for both flatbreads. Sahari, Mohammadi, and Hamidi Esfehani (2014) also showed that with increasing the shelf life of the “Taftoon” flatbread, its Kramer shear force and its firmness levels increased. Izadi Najafabadi, Hamdami, Le‐Bail, Monteau, and Keramat (2015) also reported that baking temperature had a considerable effect on the shearing force of the “Sangak” flatbread.…”
Section: Resultsmentioning
confidence: 96%